2011
DOI: 10.1159/000324129
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nuclear Receptors in the Biliary Epithelium

Abstract: The biliary epithelium is organized as a single layer of biliary epithelial cells lining the biliary tree. Biliary epithelial cells have three major biological functions: protection, secretion and proliferation. These functions are all controlled by nuclear receptors. The biliary tree conveys bile, a complex fluid containing toxics such as endotoxins, from the liver to the duodenum. Active protection against endotoxins can be elicited by the vitamin D receptor or the farnesoid X receptor (FXR), thus avoiding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 99 publications
1
6
0
Order By: Relevance
“…[17][18][19][20][21][22][23] NRs are differentially expressed in distinct liver cell types. 24,26 We found that primary cholangiocytes isolated from WT and CFTR-defective mice express multiple receptors, including VDR, LXR-b, FXR, and all three isoforms of PPAR, consistent with previously published data. 26 Conflicting reports have described PPARc expression in CF.…”
Section: Ppar-c Stimulation In Vivo Reduces Biliary Damage and Inflamsupporting
confidence: 91%
See 2 more Smart Citations
“…[17][18][19][20][21][22][23] NRs are differentially expressed in distinct liver cell types. 24,26 We found that primary cholangiocytes isolated from WT and CFTR-defective mice express multiple receptors, including VDR, LXR-b, FXR, and all three isoforms of PPAR, consistent with previously published data. 26 Conflicting reports have described PPARc expression in CF.…”
Section: Ppar-c Stimulation In Vivo Reduces Biliary Damage and Inflamsupporting
confidence: 91%
“…In the liver, NRs are expressed by different cellular subtypes, such as hepatocytes, stellate cells, macrophages, and cholangiocytes, with each displaying a specific expression pattern . By real‐time polymerase chain reaction (PCR) analysis, we compared the expression of different NRs in primary cholangiocytes isolated from WT and Cftr‐KO mice, cultured on Transwell inserts and grown as polarized monolayers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More broadly, suppression of FXR and GR may also inhibit biliary secretion, leading to toxic effects on liver cells and potentially influencing the development of colangiopathies 50 . Interestingly, UDP-glucornosyl transferase (UGT1A1), a key enzyme in bile acid synthesis was one of the non-nuclear proteins that were consistently identified in our analysis with less abundance in Atp7b −/− , implying attenuation of bilirubin and steroid conjugation with UDP-glucoronate and attenuation of bile secretion across the canalicular membrane 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation can be controlled by nuclear receptors such as the GR, FXR or the PPARs in various epithelial cells (30). Recently, a phosphatidylcholine (PC), 16: 0-18: 1 PC, was identified as the endogenous ligand of PPARα (31).…”
Section: Discussionmentioning
confidence: 99%